EVALUATION OF YIELD AND NUTRITIONAL COMPONENTS OF SOME HYBRIDS AND PARENTAL GENOTYPES OF SWEET POTATO (Ipomoea batata L.) - AFOLABI, M. S.; AGBOWURO, G. O.; ABIMBOLA, O.O.; AFUAPE, S.O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The potential of sweet potatoes to address food insecurity, malnutrition and poverty in Africa has been acknowledged. The present study was therefore conducted to evaluate some parent genotypes, hybrids and local varieties for acceptable levels of provitamin A and other micronutrients root yield characteristics and assess the relationship among traits. Twenty sweet potato genotypes including eight parental varieties, ten hybrids and two local checks used as control. The experiments were arranged in a randomized complete block design with three replicates in each year. Data on root weight per plant, root yield, and number of roots per plant were recorded at harvest. The laboratory studies involved the determination of the approximate composition of parents, hybrids and the local sweet potato genotypes. Among the hybrids, beta carotene ranged from 0.54 mg/100g fresh root (SPU26) to 1.01 mg/100g fresh root for SPU14, while in parents, it ranged between 0.42 mg/100g fresh root for Blesbok and 0.57 mg/100g fresh root for Excel. The trend was comparable to that of iron content with a range of 1.7 mg/100g fresh root for SPU17 to 2.4 mg/100g fresh root for SPU14, 1.2 mg/100g fresh root for blesbok to 1.9 mg/100g fresh root for ex-oyunga and 1.15 mg/100g fresh root for Offa 1 to 1.24 mg/100g fresh root for ex-igbariam in the hybrids and parents, respectively. The highest root yield of 60.23t/ha was recorded for SPU02 among the hybrids, and resist recorded the highest yield (31.32 t/ha) among the parents and ex-igbariam among the checks. Therefore, breeders could find nutritional attributes useful for genetic manipulation and cultivar development for enhanced provitamin A, other micronutrients and yield parameters.